2023
DOI: 10.24272/j.issn.2095-8137.2022.384
|View full text |Cite
|
Sign up to set email alerts
|

A 1.1 Mb duplication CNV on chromosome 17 contributes to skeletal muscle development in Boer goats

Abstract: The Boer goat is one of the top meat breeds in modern animal husbandry and has attracted widespread attention for its unique growth performance. However, the genetic basis of muscle development in the Boer goat remains obscure. In this study, we identified specific structural variants in the Boer goat based on genome-wide selection signals and analyzed the basis of the molecular heredity of related candidate genes in muscle development. A total of 9 959 autosomal copy number variations (CNVs) were identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…All of these proteins are closely related to the known function of the PLEC. CNVs may potentially affect gene expression by altering gene dose and transcriptional structure [41]. Alterations in the copy number of this extensive coding sequence suggest that, irrespective of the copy number itself, the presence of multiple copies may lead to the deterioration of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…All of these proteins are closely related to the known function of the PLEC. CNVs may potentially affect gene expression by altering gene dose and transcriptional structure [41]. Alterations in the copy number of this extensive coding sequence suggest that, irrespective of the copy number itself, the presence of multiple copies may lead to the deterioration of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SVs can be divided into two types based on changes in the DNA content of the genome: 1) unbalanced copy number variants (CNVs), including deletions (DELs), duplications (DUPs), insertions (INSs), and mobile element insertions (MEIs); and 2) balanced rearrangements, including inversions (INVs) and translocations (TRAs) [ 3 ]. In livestock research, SVs have been shown to be associated with adaptability and production traits [ 4 , 5 ]. Compared to SNPs, SVs contribute to a higher proportion of complex phenotypes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%